Precision luminosity measurements at LHCb - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Grünberg, Oliver; Han, Xiaoxue; et al. (Journal of Instrumentation, 2014)
Measuring cross-sections at the LHC requires the luminosity to be determined accurately at each centre-of-mass energy √s. In this paper results are reported from the luminosity calibrations carried out at the LHC interaction point 8 with the LHCb detector for √s = 2.76, 7 and 8 TeV (proton-proton collisions) and for √sNN = 5 TeV (proton-lead collisions). Both the "van der Meer scan" and "beam-gas imaging" luminosity calibration methods were employed. It is observed that the beam density profile cannot always be described by a function that is factorizable in the two transverse coordinates. The introduction of a two-dimensional description of the beams improves significantly the consistency of the results. For proton-proton interactions at √s = 8 TeV a relative precision of the luminosity calibration of 1.47% is obtained using van der Meer scans and 1.43% using beam-gas imaging, resulting in a combined precision of 1.12%. Applying the calibration to the full data set determines the luminosity with a precision of 1.16%. This represents the most precise luminosity measurement achieved so far at a bunched-beam hadron collider.
*The LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, S. Bachmann, A. Bien, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelelov [und sehr viele weitere Personen]
Gesehen am 05.10.2020